This is an exercise from Jack K.Hales book on ODEs

Let $X=C^1([0,1],\mathbb{R}^n) \times [0,1]$ and consider $$ w:X\longrightarrow \mathbb{R}^n $$ where $w(f,t)=f(t)\in \mathbb{R}^n$. The point is to show that $w$ is Frechet differentiable and calculate it's derivative.

Some thoughts are that if we fix $f\in C^1([0,1],\mathbb{R}^n)$ then $$ |f(t+h)-f(t)+D_{t}(f)h|\leq r(t,h) $$ with $\frac{ r(t,h)}{h}\longrightarrow 0$ for some function $r$ and $D_{t}(f)$ denoting the total derivative of the vector valued $f$ at $t$.

Now would it be correct to define the operator $$ D:X\longrightarrow \mathbb{R}^n $$ with $D(f,t)=D_{t}(f)$ to be the Frechet derivative of $w$?


The way you started is unfortunately wrong. The Frechet derivative of $w$ is $ Dw((f,t)) = (\delta_t , f'(t))$. Just for clarification how to interpret this equality: $$Dw((f,t))(g,s) = \big(\delta_t , f'(t)\big)\,(g,s) = g(t) + f'(t)s.$$

Calculating the Frechet derivative

First of all we need a norm on $X$. I suggest $$\|(f,t)\|_X := \|f\|_\infty + \|f'\|_\infty + |t|$$ where $f'$ denotes the derivate of $f$ and $\|g\|_\infty = \sup_{s\in[0,1]} \|g(s)\|_p$ for any $p$-norm on $\mathbb{R}^n$.

Recall an equivalence of the definition of Frechet derivative:

Let $\phi: X \to Z$ and $D\phi : X \to L(X,Z)$ then $D\phi$ is the Frechet derivate of $\phi$ if $$\|\phi(x+y) - \phi(x)- D\phi(x)y\|_Z \in o(\|y\|_X)\tag{1}$$

In our case we have that each $x\in X$ has the representation $(f,t)$. An educated guess for the Frechet Derivate of $w$ is $$Dw(x)y = Dw((f,t)) (g,s) = \big(\delta_t, f'(t) \big)(g,s) = g(t) + f'(t)s$$ This comes from regarding $w(x+y)-w(x)$.

In order the show that our guess is in fact the Frechet derivative we will show the condition $(1)$. Let $x = (f,t) \in X$ and $y=(g,s) \in X$ \begin{align} \|w(x+y)-w(x) - Dw(x)y \|_p &= \|(f+g)(t+s)-f(t) - g(t) - f'(t)s\|_p \\ &= \|f(t+s) + g(t+s) - f(t) - g(t) - f'(t)s\|_p \\ &\leq \|f(t+s) - f(t) - f'(t)s\|_p + \|g(t+s) - g(t)\|_p \end{align} Since $\|y\|_X = \|g\|_\infty + \|g'\|_\infty + |s|$ we have from the well-known properties of differentiable functions that \begin{align} \|f(t+s) - f(t) - f'(t)s\|_p \in o(|s|) \subseteq o(\|(g,s)\|_X) \end{align} and \begin{align} \|g(t+s) - g(t)\|_p = \|g'(t)s + o(s)\|_p \in o(\|(g,s)\|_X) \end{align} which gives us that also the sum is in $o(\|(g,s)\|_X) = o(\|y\|_X)$. Hence we showed $(1)$ and consequently the desired statement.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.